Formation of ZrO2 gate dielectric on Ge substrate by thermal oxidation and post annealing for metal-oxide-semiconductor devices / Lei Zhen Ce - Lei , Zhen Ce (2019)
Sputtered pure zirconium (Zr) metal films on germanium (Ge) substrates were thermally oxidized/nitrided at various temperatures (300 – 800 °C) for 15 minutes. Furthermore, some of the samples performed post oxidation annealing at various temperatures (400 – 800 °C). Effects of thermal oxidation/nitridation/post annealing in oxygen (O2), nitrous oxide (N2O), nitrogen (N2) and argon (Ar) gas ambient on the physical and electrical properties of zirconium dioxide (ZrO2) thin films were investigated. For the samples oxidized in O2, J-E characteristics results showed that the leakage current of oxidation temperature above 600 °C was significantly higher than below 600 °C. X-Ray Diffraction (XRD), Raman spectroscopy, and Fourier Transform Infrared (FTIR) spectroscopy results showed the presence of germanium dioxide (GeO2) compounds in the samples above 600 °C. X-Ray Photoelectron Spectroscopy (XPS) analysis showed the sample at 500 °C was closest to full oxidation, while electrical characterization, particularly leakage current density – electric field (J-E) characteristics, showed that the 500 °C sample has the highest electrical breakdown field. For the samples that have been oxidized/nitrided in N2O, the ZrO2 dielectric film was unstable for temperatures above 700 °C, which was higher than O2 ambient, possibly due to the activation energies of N2O are higher than O2. XPS analysis showed that the Ge atoms accumulated at both sides of ZrO2 dielectric and the 400 °C sample was closest to full oxidation. The J-E characterization has shown that the 400 °C sample has the highest electrical breakdown field. For the annealed samples, the ZrO2 dielectric film was unstable for temperatures above 700 °C. It may be due to the samples which are very sensitive to O2 at high temperatures which reacted with the residues of O2. For all samples above 700 °C, the Williamson-Hall (W-H) plot analysis showed two types of GeO2 crystallite size and microstrain were found which indicated that there are two generating sources for GeO2.Two main possible mechanisms have been proposed and explicated in this thesis. The first mechanism is the thermal oxidation related to the diffusion of O2 or N2O through the ZrO2 layer and the formation of GeO2, while the other proposed mechanism is the Ge atomic diffusion and its rearrangement in ZrO2.